In vivo infection by a neuroinvasive neurovirulent dengue virus (2012)
Although neurological manifestations associated with dengue infections have been reported in endemic countries, the viral or host characteristics determining the infection or alteration of nervous function have not been described. In order to investigate neurobiological conditions related to central nervous system dengue virus (DENV) infection, we established a mouse model of neuroinfection. A DENV-4 isolate was first adapted to neuroblastoma cells, later inoculated in suckling mice brain, and finally, this D4MB-6 viral variant was inoculated intraperitoneally in Balb/c mice at different postnatal days (pnd). Virusinduced fatal encephalitis in 2 and 7 pnd mice but infected at 14 and 21 pnd mice survived. The younger mice presented encephalitis at the sixth day postinfection with limb paralysis and postural instability concomitant with efficient viral replication in brain. In this mice model, we found activated microglial cells positive to viral antigen. Neurons, oligodendrocytes, and endothelial cells were also infected by the D4MB-6 virus in neonatal mice, which showed generalized and local plasma leakage with blood-brain barrier (BBB) severe damage. These results suggest that there was a viral fitness change which led to neuroinfection only in immune or neurological immature mice. Infection of neurons, endothelial, and microglial cells may be related to detrimental function or architecture found in susceptible mice. This experimental neuroinfection model could help to have a better understanding of neurological manifestations occurring during severe cases of dengue infection.